Richness, composition and abundance of species in a riparian plant community in the Santa Catarina river, Monterrey, Nuevo León - Mata-Balderas, José Manuel (Universidad Autónoma de Tamaulipas, 2020)
Riparian vegetation constitutes a key element for the maintenance of fluvial ecosystems, especially for those that are surrounded by urban zones. The aim of this study was to evaluate the composition and variation of riparian vegetation in a stretch of the Santa Catarina river, over two cities of the Monterrey Metropolitan Area. For the analysis of the vegetation, sampling transects were established in a section of 15.65 km. The high stratum (shrub and tree plants) was analyzed using a Bray-Curtis ordering model and a dominance-diversity plot. The Jaccard similarity coefficient was used for the low stratum (herbaceous plants). In the high stratum, 16 families belonging to 25 genera and 28 species were recorded. The species with the highest number of individuals were Salix nigra, Leucaena leucocephala, Ricinus communis and Parkinsonia aculeata. The composition of the vegetation has a similarity level of intermediate to high, because the groups vary between 60 % to 71.53 %. In thelow stratum, 25 families, 53 genera and 60 species were recorded with a similarity level of low to intermediate, because the groups vary between 23 to 47 %. The species that were mostly registered in the low stratum were Cyperus involucratus in 7 sites, and Eragrostis mexicana, Heliantus annuus,Melinis repens, Polygonum pensylvanicum and Typha domingensis in six sites each one. The composition of the vegetation is in a secondary successional state, because the species with greater presence are exotic or invasive, such as Leucaena leucocephala and Ricinus communis for the high stratum and Cyperus involucratus, Typha domingensis and Melinis repens for the low stratum.